Transit Migration: All Roads Lead to America. (29th January 2018) - Artuc, Erhan; Ozden, Caglar
Abstract : The paths of many migrants include multiple destinations and transit routes, yet this pattern is almost never reflected in empirical analyses. For example, 9% of recent immigrants to the US arrived from a transit country as opposed to the one they were born in. Among those arriving from many OECD countries, transit migration ratio exceeds 30%. To explain these patterns, we construct a dynamic model of global migration that allows transit migration opportunities to impact the attractiveness of locations. After estimating structural parameters of the model, we simulate various counterfactual scenarios to highlight the spillovers of transit migration paths.